Role of Anterior Segment OCT in the Management of Primary Narrow Angle Disease: Doi:10.36351/pjo.v36i4.1039 - Muid, Javeria; Farooq, Sadia (Pakistan Journal of Ophthalmology, 2020)
Purpose: To highlight the role of anterior segment OCT, in complementing gonioscopic findings in the management of angle closure glaucoma. Study Design: Descriptive observational case series. Study Place and Duration: Study was conducted at Eye department of Shifa International Hospital, from January 2019 to March 2019. Methods: After taking informed consent from the patients, the study was conducted at Shifa International Hospital Islamabad. Patients were selected by convenient sampling technique. Patients were diagnosed on the basis of history and clinical examination. Patients with angle closure on Gonioscopy were included in this series. Detailed ocular examination including visual acuity for distance and near, tonometry, Gonioscopy and anterior segment OCT were performed. Data was collected and presented as case series. Results: The median age 57 years with 50% more than 60 years and 50% less than 60 years of age. Presenting IOP was less than 21 mmHg in 50% and higher in remaining 50%. On examination 37.5% were categorized as PACS, 12.5% having PAC and 50% as PACG. After definitive treatment 12.5% still needed medical treatment to prevent progression in PACG and none in PACS and PAC. Conclusion: In narrow angle disease, treatment is designed not only to control intraocular pressure (IOP) but also to keep angle open as much as possible. Appositional closure or peripheral anterior synechiae (PAS) can damage the trabecluar meshwork. Iridoplasty, peripheral Iridotomy (PI) and early lens extraction can defer the need for filtration procedure if done well in time. Key Words: OCT anterior segment, Narrow angle, Optic nerve head.